2018
DOI: 10.1108/jamr-05-2017-0061
|View full text |Cite
|
Sign up to set email alerts
|

Social media research in the context of emerging markets

Abstract: Purpose: Despite the potential of social media in emerging markets (EMs), only few studies published in high quality information systems (IS) journals that have addressed issues related to social media in the context of EMs. This study aims to analyse existing research related to social media published in high quality IS journals for exploring initial research trends, emerging themes, limitations and future research directions in the context of emerging markets. Design/methodology/approach: This study conducte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

5
4

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…In recent times, in the domain of IS, psychology, and sociology, it is observed that a plethora of theoretical models have been developed for exploring and predicting users' acceptance of IS. Among these models, many researchers advocated in favour of Technology Acceptance Model (TAM) [22][23][24][25]. But on the contrary, some scholars observed that TAM has some specific drawbacks [26].…”
Section: Overview Of Technology Acceptance Theories and Modelsmentioning
confidence: 99%
“…In recent times, in the domain of IS, psychology, and sociology, it is observed that a plethora of theoretical models have been developed for exploring and predicting users' acceptance of IS. Among these models, many researchers advocated in favour of Technology Acceptance Model (TAM) [22][23][24][25]. But on the contrary, some scholars observed that TAM has some specific drawbacks [26].…”
Section: Overview Of Technology Acceptance Theories and Modelsmentioning
confidence: 99%
“…Platforms like Twitter and Facebook has been an integral part of our daily existence and have become entrenched in our daily routines and are now considered indispensable. [1], [2], [3], [4], [5], [6],. Twitter, in particular, is a highly favored platform for sharing brief messages, known as tweets, which are limited to 280 characters.…”
Section: Introductionmentioning
confidence: 99%
“…The use of social media has developed from media to communicate to become more diverse, including in communicating and marketing products. Social media usage makes it interactive between producers and consumers and consumers and consumers (Tamilmani et al, 2018).…”
Section: Introductionmentioning
confidence: 99%